Classifying acoustic signals into phoneme categories: average and dyslexic readers make use of complex dynamical patterns - Hasselman, Fred (PeerJ PrePrints, 2014)
Aetiologies of developmental dyslexia often assume a deficit in auditory processing may be causally entailed in the specific learning disorder. The purpose of this study is to compare a number of assumed auditory features that are supposed to evidence the account given by such aetiologies under conditions of strong inference. To do so, the relevant acoustic features were extracted from the same set of artificial speech stimuli that lie on a /bAk/-/dAk/ continuum. Features were tested on their ability to enable a simple classifier (Quadratic Discriminant Analysis) to reproduce the observed classification performance of average and dyslexic readers in a speech perception experiment. The ‘classical’ features examined were based on component process accounts of developmental dyslexia such as the supposed deficit in Envelope Rise Time detection and the deficit in the detection of rapid changes in the distribution of energy in the frequency spectrum (formant transitions). Studies examining these temporal processing deficit hypotheses remarkably do not employ measures that quantify the temporal dynamics of stimuli. It is shown that measures based on quantification of the dynamics of complex, interaction-dominant systems enable QDA to classify the stimuli almost identically as dyslexic and average reading participants. It seems unlikely that participants used any of the features that are traditionally associated with accounts of (impaired) speech perception that assume classifying speech stimuli amounts to a linear additive interaction of component processes that each parse the acoustic signal independent of one another.
Keywords: Speech Perception; Developmental Dyslexia; Recurrence Quantification Analysis; Theory evaluation; Rise Time Perception Deficit; Strong Inference; Auditory Temporal Processing Deficit; Pattern Classification; Complexity Science; aetiology